Comparative proteomics analysis of spermary and ovary in Hyriopsis schlegelii. Issue 3 (4th March 2017) - Shi, Jianwu; Wang, Dexia; Zhou, Yan; Gu, Yiran; Wu, Di; Wang, Junhua; Hong, Yijiang
Abstract: We provide the first large-scale quantitative proteomics analysis in Hyriopsis schlegelii . To investigate the proteins expressed in the gonads, a quantitative proteomics approach has been utilized to analyze differentially expressed proteins between the spermary and ovary. In this study, we identified and quantified 2416 proteins in the gonads of Hyriopsis schlegelii . Of these, 559 proteins showed significantly different expression between the spermary and ovary. Some specific proteins expressed in either the spermary or ovary were identified in Hyriopsis schlegelii . In addition, a series of proteins related to gametogenesis were also identified. Compared with previous reports, many proteins in Hyriopsis schlegelii identified here have different expression patterns between the spermary and ovary. The special hermaphroditism in Hyriopsis schlegelii may contribute to these inconsistent results. The provided proteomics data could be considered as a starting point for subsequent studies focusing on the proteins involved in sexual gland development and maturity. Graphical abstract: : The distribution of 2416 proteins based on the differential expression between spermary and ovary.